THE EFFECTIVENESS OF DEVELOPING STUDENT WORKSHEETS BASED ON CAT TO IMPROVE THE STUDENTS’ ABILITY TO COMPREHEND MATHEMATIC AT GRADE VI SD METHODIST-12 MEDAN - Patri Janson Silaban; Asnita Hasibuan (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The ability to comprehend mathematics can be trained and improved in each student. Students Worksheet (LKPD) refers to a learning aid in the learning process. CAT (Computer Assisted Test) is one of the learning media designed to develop interactive LKPD. This research employed the Research and Development method. Based on the evaluation conducted by material experts in the field of mathematics education, the results for content feasibility, presentation, language, and graphics reached 88.02%, which was categorized as very good. Furthermore, the evaluation results from media experts showed that the percentage for media feasibility, content feasibility, presentation, and graphics was 90.73% (very good). In addition, media experts also stated that the percentage of media feasibility, content feasibility, and presentation aspects reached 95.00% (very good). Moreover, the results of the individual test on students’ responses indicated that the aspects of content, objectives, feasibility, technical quality, and attractiveness achieved 92.00% (very good). The field test results on students’ responses showed that the percentage for content, objectives, technical quality, and attractiveness aspects was 94.77% (very good). Finally, the data analysis of individual student response tests confirmed that the aspects of content, objectives, feasibility, quality, and attractiveness reached 92.00%, which was categorized as very good.